2015
DOI: 10.1146/annurev-physiol-021014-071704
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Body Fat in Caenorhabditis elegans

Abstract: Studies conducted in C. elegans over the last decade highlight the ancient and complex origins of body fat regulation. In this critical review, I introduce the major functional approaches used to study energy balance and body fat, the lipid composition of C. elegans, the regulation of cellular fat metabolism and its transcriptional control. Next I describe the influence of the sensory nervous system on body fat and the major regulatory mechanisms that couple food perception in the nervous system with the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 95 publications
3
107
0
Order By: Relevance
“…and S.S., unpublished observations). We have previously shown that a substantial loss of body fat requires the transcriptional induction of the atgl-1 lipase (Noble et al, 2013; Srinivasan, 2015). In keeping with the differential effects of oxygen exposure on body fat loss, we found that upon fasting, the extent to which atgl-1 is transcriptionally induced is dependent upon exposure to oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and S.S., unpublished observations). We have previously shown that a substantial loss of body fat requires the transcriptional induction of the atgl-1 lipase (Noble et al, 2013; Srinivasan, 2015). In keeping with the differential effects of oxygen exposure on body fat loss, we found that upon fasting, the extent to which atgl-1 is transcriptionally induced is dependent upon exposure to oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…In C. elegans , food sensory cues influence nearly all aspects of behavior and physiology including sensory functions, locomotion, reproduction, metabolism and lifespan (Lemieux and Ashrafi, 2015; Srinivasan, 2015). Food presence is encoded by two major neuroendocrine systems: serotonin (5-hydroxytryptamine, 5-HT) and transforming growth factor beta (TGF-β) (Entchev et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Additional similarities include neuroendocrine pathways such as insulin and steroid hormone signaling as well as neuromodulators, for example, serotonin and dopamine, and feeding regulatory neuropeptides such as oxytocin and opioid-like peptides [4,5,9]. As in mammals, the nervous system of C. elegans integrates both external and internal cues to modulate behavior but also peripheral physiology via hormone secretion [5,10,11].…”
Section: Overview Of C Elegans Energy Balance Pathwaysmentioning
confidence: 99%
“…elegans is a small worm with a life expectancy of about 21 days that has rapid growth and feeds on non-pathogenic strains of Escherichia coli [11][12][13][14]. It's a little worm from all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…It's a little worm from all over the world. As newly hatched larvae are 0.25 millimeters in length and adults 1 millimeters in length ( Figure 1) [11,14]. In stage L4, hermaphrodites have a conical tail and a developing vulva (white arrowhead) can be seen as a clear half-circle in the center of the ventral side.…”
Section: Introductionmentioning
confidence: 99%